Genome-Wide Association Study Reveals Four Loci for Lipid Ratios in the Korean Population and the Constitutional Subgroup - Kim, Taehyeung (PLoS One, 2017)
Circulating lipid ratios are considered predictors of cardiovascular risks and metabolic syndrome, which cause coronary heart diseases. One constitutional type of Korean medicine prone to weight accumulation, the Tae-Eum type, predisposes the consumers to metabolic syndrome, hypertension, diabetes mellitus, etc. Here, we aimed to identify genetic variants for lipid ratios using a genome-wide association study (GWAS) and followed replication analysis in Koreans and constitutional subgroups. GWASs in 5,292 individuals of the Korean Genome and Epidemiology Study and replication analyses in 2,567 subjects of the Korea medicine Data Center were performed to identify genetic variants associated with triglyceride (TG) to HDL cholesterol (HDLC), LDL cholesterol (LDLC) to HDLC, and non-HDLC to HDLC ratios. For subgroup analysis, a computer-based constitution analysis tool was used to categorize the constitutional types of the subjects. In the discovery stage, seven variants in four loci, three variants in three loci, and two variants in one locus were associated with the ratios of log-transformed TG:HDLC (log[TG]:HDLC), LDLC:HDLC, and non-HDLC:HDLC, respectively. The associations of the GWAS variants with lipid ratios were replicated in the validation stage: for the log[TG]:HDLC ratio, rs6589566 near APOA5 and rs4244457 and rs6586891 near LPL; for the LDLC:HDLC ratio, rs4420638 near APOC1 and rs17445774 near C2orf47; and for the non-HDLC:HDLC ratio, rs6589566 near APOA5. Five of these six variants are known to be associated with TG, LDLC, and/or HDLC, but rs17445774 was newly identified to be involved in lipid level changes in this study. Constitutional subgroup analysis revealed effects of variants associated with log[TG]:HDLC and non-HDLC:HDLC ratios in both the Tae-Eum and non-Tae-Eum types, whereas the effect of the LDLC:HDLC ratio-associated variants remained only in the Tae-Eum type. In conclusion, we identified three log[TG]:HDLC ratio-associated variants, two LDLC:HDLC ratio-associated variants, and one non-HDLC:HDLC-associated variant in Koreans and the constitutional subgroups.